2022
DOI: 10.1007/s10872-021-00624-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of turbulent diapycnal mixing along the Mindanao current inferred from rapid-sampling Argo floats

Abstract: The Mindanao Current (MC) bridges the North Pacific low-latitude western boundary current system region and the Indonesian Seas by supplying the North Pacific waters to the Indonesian Throughflow. Although the previous study speculated that the diapycnal mixing along the MC might be strong on the basis of the water mass analysis of the gridded climatologic dataset, the real spatial distribution of diapycnal mixing along the MC has remained to be clarified. We tackle this question here by applying a finescale p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…By staying submerged throughout their deployment, reporting their position and data every 10‐days, the path of these floats can resolve the dynamic and time‐evolving structure of mesoscale features such as boundary currents and subsurface eddies (Armi et al, 1989; Collins et al, 2013). They are integral to studying physical process such as diapycnal mixing (He et al, 2022). The Argo Program's global scope and long record has been key to quantifying the accumulation of heat in the deep ocean due to climate change (Hansen et al, 2011).…”
Section: Measuring Ocean Currentsmentioning
confidence: 99%
“…By staying submerged throughout their deployment, reporting their position and data every 10‐days, the path of these floats can resolve the dynamic and time‐evolving structure of mesoscale features such as boundary currents and subsurface eddies (Armi et al, 1989; Collins et al, 2013). They are integral to studying physical process such as diapycnal mixing (He et al, 2022). The Argo Program's global scope and long record has been key to quantifying the accumulation of heat in the deep ocean due to climate change (Hansen et al, 2011).…”
Section: Measuring Ocean Currentsmentioning
confidence: 99%
“…Concomitantly, the long‐range radiation and interference of multisource internal tides result in complex dissipation distribution (Y. Wang et al., 2018, 2021). Besides the internal tides, previous studies have indicated other dynamic factors contributing to the inhomogeneous spatial distribution of mixing in the Northwestern Pacific, including parametric subharmonic instability (PSI; Qiu et al., 2012), wind‐induced near inertial motions (Jing & Wu, 2010; Jing et al., 2011; Whalen et al., 2012), mesoscale eddies (Jing et al., 2011; Whalen et al., 2018; You et al., 2021), and large‐scale currents (He et al., 2022; Liu et al., 2017; Yang et al., 2014). However, most of these results focus primarily on the upper layer, with insufficient attention given to abyssal mixing due to the lack of deep‐sea observations.…”
Section: Introductionmentioning
confidence: 99%